PERUBAHAN LUASAN TUTUPAN MANGROVE PADA TAHUN 2008, TAHUN 2013 DAN TAHUN 2018 DI MANDEH KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - weni putri; Triyatno Triyatno (JURUSAN GEOGRAFI FIS UNP, 2021)
This research aims to : 1)to find out the distribution land cover of mangrove forest in the Mandeh Koto XI Tarusan area in 2008, 2013 and 2018. 2) Identify changes in the extent of mangrove forest land cover in the Mandeh area in 2008, 2013 and 2018. 3) to know out types of mangrove course in Mandeh Koto XI Tarusan in 2018. This type of research is quantitative by using a descriptive approach that is by interpreting remote sensing imagery and fieldwork of researchers using the supervised method (supervised) The results of the research are: 1) the distribution of mangrove land cover in the Mandeh area in 2008, there were 577,79 Ha spread over Ha in Ampang Pulai and 95,28 Ha in Mandeh. in 2013 there were 547,26 Hapread in Mandeh 88,48 Ha and Ampang Pulai 340,57 hectares. and 2018 which spread 724,74 Ha and found in the Ampang Pulai area at 387,52 Ha and in the Mandeh area 84,29 Ha. 2) analysis of changes in mangrove forest cover year 2008 to 2013 showed a reduction in the area from 577,79 hectares to 547,26 hectares reduced by 30,53 Ha and in 2013 to 2018 showed a very significant change from 547,26 hectares to 724,74 hectares reduced by 177,48 Ha. 3) the types of mangroves in the Mandeh area, namely: Rhizophora Apiculata (Mangrove), Nypah Fruticans, Rhizophora Mucronata, and Rhizophora stylosa. Image accuracy test is done using confusion matrix (comparison of image interpretation with field conditions) with an accuracy rate the year 2008 is 82,3% the year 2013 is 80,3 %the year 2018 is 86,2%.